Nutritional Knowledge, Attitude and Practice among Antenatal and Postnatal Mothers in Hospital Tengku Ampuan Afzan (Htaa), Kuantan, Pahang 2016 - Ikhsan, Liyana Nabihah; Nasaruddin, Nur Asifa Mohd; Othman, Farhana; Abd Aziz, Karimah Hanim; Ismail, Hamizah (IIUM Medical Journal Malaysia, 2018)
Background: Balanced and sufficient maternal nutritional intake ensures not only the wellbeing of pregnant mother, fetus, and newborn (protection of life) but also her future health and her three generations (protection of progeny). Nutritional inadequacies during pregnancy have been reported and several factors were attributed. The objectives were to measure nutritional knowledge, attitude, and practice (KAP) during pregnancy and the relationship with socio-demographic characteristics. Methods: A cross-sectional study was conducted among 320 antenatal and postnatal mothers in Hospital Tengku Ampuan Afzan (HTAA), Pahang, Malaysia from 18th July to 27th August 2016. A pre-tested self-constructed, interview-guided questionnaire was used. Independent variables were age, ethnicity, educational level, marital status, and monthly household income. Outcomes were nutritional KAP-level with median used for the categorization. The relationship between independent variables and outcomes was obtained by logistic regression with significance at p<0.05. Results: Sixty-five percent aged from 25 to 34, 84% Malays, 37% completed secondary education with SPM/O-level, 96% married, 48% from middle-income family, 52% had a good nutritional knowledge, 67% with a positive attitude and 55% with good practice. Age and educational level were significantly related to knowledge. The only educational level was significantly related to practice. Less than 70% of respondents have good nutritional KAP, reflected by educational level with more than half of them received up to secondary education. Hence, the rights of mothers in getting a necessary and adequate education should be fulfilled. Conclusion: Results emphasize the importance of empowering girls and women with adequate educations and to strengthen the nutritional and health education of our educational system. It is for them to be knowledgeable with good attitude and practicing healthy nutritional lifestyle as they entering reproductive life, maintaining and transferring at least optimum healthy life to their progenies.